The application of the experiential learning approach in english as a secnd language at UDELAS University - Miranda S., Iliana Maribel; Miranda Samudio, Luz Elena; Boungarden, Nelly; Quintero, Lourdes; Acosta, Jorge (David, Panamá : UDELAS, 2011)
This research focuses on the experiential learning approach and how it provides important advantages in the english teaching process. Learning a second language is becoming more important in a globalizing world.
GENERAL INDEX Chart index Graph index Dedication Acknowledgment Introduction Chapter 1: Background Chapter 2: Theoretical framework 2. The application of experimentaial learning apporach for teaching english as a second language at UDELAS University 2.1. Experietial learning approach history 2.1.2. 20th century theories of learning and a comparison through the years in the english teaching process 2.1.3. Concept of experiential learning approach 2.1.4. Teaching with experintial learning approach 2.1.5. The sue of experiential learning approach need 2.1.6. Using the experiential approach to teach english as a second language And others more Chapter 3: Methodological framework Chapter 4: Analysus of result Conclusion Recommendations References Annex
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; ESCUELA DE EDUCACIÓN SOCIAL Y ESPECIAL; ENGLISH DEPARTMENT; LICENCIATURA EN DOCENCIA EN INGLÉS